The Relationship Between Personal Ethics and Organizational Citizenship Behavior: A Case of PT. Toa Galva Industries, Jakarta. - Darmawan, Suteja Febby (2006)
The purpose of this study was to explore the Organizational Citizenship Behaviour (OCB) practices among employee in manufacturing institution, and to determine the relationship between demographic factor and personal ethics to OCB. Moreover, this study also tries to determine whether the dimensions of personal ethics moderate the relationship with OCB. Data were collected fiom 130 employees by using stratified random sampling to ensure that every department was represented in fiom one telecommunication companies this study. A questionnaire consisting of 61 questions was administered to the respondents. The study showed that employee does display OCB, with high altruism and conscientiousness but in courtesy has lowest. The employees also do display personal ethics with high in social participation but low in functional participation. Demographic factor were not found to be related to OCB but age and experience well related to personal ethics. The study also found that the dimensions of Personal Ethics influenced OCB and dimension of OCB and the dimension of personal ethics are related significantly.